2015
DOI: 10.1136/gutjnl-2014-308506
|View full text |Cite
|
Sign up to set email alerts
|

PHLDA3 overexpression in hepatocytes by endoplasmic reticulum stress via IRE1–Xbp1s pathway expedites liver injury

Abstract: ObjectiveEndoplasmic reticulum (ER) stress is involved in liver injury, but molecular determinants are largely unknown. This study investigated the role of pleckstrin homology-like domain, family A, member-3 (PHLDA3), in hepatocyte death caused by ER stress and the regulatory basis.DesignHepatic PHLDA3 expression was assessed in HCV patients with hepatitis and in several animal models with ER stress. Immunoblottings, PCR, reporter gene, chromatin immunoprecipitation (ChIP) and mutation analyses were done to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
61
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 32 publications
6
61
1
1
Order By: Relevance
“…Activated IRE1α splices XBP1 mRNA, which encodes transcription factor to increase the protein-folding capacity and degrade misfolded proteins. While IRE1α engages STAT3 pathway to promote liver regeneration upon liver injury 26 , XBP1 switches prosurvival to proapoptotic signal cascades through multiple gene regulation 27,28 . It has been reported that ATF6 exerts a pro-inflammatory effect on ischemiareperfusion liver injury 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Activated IRE1α splices XBP1 mRNA, which encodes transcription factor to increase the protein-folding capacity and degrade misfolded proteins. While IRE1α engages STAT3 pathway to promote liver regeneration upon liver injury 26 , XBP1 switches prosurvival to proapoptotic signal cascades through multiple gene regulation 27,28 . It has been reported that ATF6 exerts a pro-inflammatory effect on ischemiareperfusion liver injury 29 .…”
Section: Discussionmentioning
confidence: 99%
“…In our recent study, ER stress marker levels were enhanced in patients with liver injury (Han et al, 2016). To confirm inflammasome activation in an animal model of liver injury, we examined liver samples from mice treated with the drug acetaminophen (APAP), which induces ER stress and liver damage (Han et al, 2016). In these liver samples, Fxr transcript levels were decreased, and Nlrp3 levels were increased relative to untreated controls ( Figure 1B).…”
Section: Hepatic Fxr Levels Inversely Correlate With Nlrp3 Inflammasomentioning
confidence: 91%
“…Intriguingly, the levels of NLRP3 and other inflammasome-associated gene transcripts (i.e., thioredoxin-interacting protein [TXNIP], apoptosis-associated speck-like caspase activation and recruitment domain (CARD)-containing protein [ASC], and caspase-1 [CASP1]) increased markedly as hepatic necrosis became severe, although FXR levels decreased ( Figure 1A). In our recent study, ER stress marker levels were enhanced in patients with liver injury (Han et al, 2016). To confirm inflammasome activation in an animal model of liver injury, we examined liver samples from mice treated with the drug acetaminophen (APAP), which induces ER stress and liver damage (Han et al, 2016).…”
Section: Hepatic Fxr Levels Inversely Correlate With Nlrp3 Inflammasomentioning
confidence: 99%
“…Each of the three proteins is linked to a distinct downstream cascade that together mitigate cellular stress and maintain homeostasis. While UPR in hepatocytes has been well studied, especially in the context of metabolic dysregulation56, its involvement in liver fibrogenesis and HSC activation is not as well-characterized789.…”
mentioning
confidence: 99%